Heterodimeric l-amino acid oxidase enzymes from Egyptian Cerastes cerastes venom: Purification, biochemical characterization and partial amino acid sequencing - A.E. El Hakim; W.H. Salama; M.B. Hamed; A.A. Ali; N.M. Ibrahim (Journal of Genetic Engineering and Biotechnology, 2015)
Two l-amino acid oxidase enzyme isoforms, Cc-LAAOI and Cc-LAAOII were purified to apparent homogeneity from Cerastes cerastes venom in a sequential two-step chromatographic protocol including; gel filtration and anion exchange chromatography. The native molecular weights of the isoforms were 115 kDa as determined by gel filtration on calibrated Sephacryl S-200 column, while the monomeric molecular weights of the enzymes were, 60, 56 kDa and 60, 53 kDa for LAAOI and LAAOII, respectively. The tryptic peptides of the two isoforms share high sequence homology with other snake venom l-amino acid oxidases. The optimal pH and temperature values of Cc-LAAOI and Cc-LAAOII were 7.8, 50 °C and 7, 60 °C, respectively. The two isoenzymes were thermally stable up to 70 °C. The Km and Vmax values were 0.67 mM, 0.135 μmol/min for LAAOI and 0.82 mM, 0.087 μmol/min for LAAOII. Both isoenzymes displayed high catalytic preference to long-chain, hydrophobic and aromatic amino acids. The Mn2+ ion markedly increased the LAAO activity for both purified isoforms, while Na+, K+, Ca2+, Mg2+ and Ba2+ ions showed a non-significant increase in the enzymatic activity of both isoforms. Furthermore, Zn2+, Ni2+, Co2+, Cu2+ and AL3+ ions markedly inhibited the LAAOI and LAAOII activities. l-Cysteine and reduced glutathione completely inhibited the LAAO activity of both isoenzymes, whereas, β-mercaptoethanol, O-phenanthroline and PMSF completely inhibited the enzymatic activity of LAAOII. Furthermore, iodoacitic acid inhibited the enzymatic activity of LAAOII by 46% and had no effect on the LAAOI activity.